Інтеграція передових методів та моделей у методології розрахунку торсіонних валів систем підресорювання легких броньованих машин (оглядова стаття) - Зінченко, Олена Іванівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
На сьогоднішній день існує протиріччя між реальними показниками міцності та довговічності та тими, які слід забезпечити для легких броньованих машин нового покоління, а особливо – майбутніх. Крім того, це протиріччя поглиблюється відсутністю поглиблених наукових методів та моделей напружено-деформованого стану, які б адекватно відобразили процеси і стани у торсіонних валах систем підресорювання легких броньованих машин, а також стали б основою розроблення заходів із підвищення їх міцності та довговічності. Проведений аналіз літературних джерел показав відсутність системного зв'язку конструктивних рішень, технологічних режимів та умов навантаження у розрахунках торсіонних валів систем підресорювання легких броньованих машин. Показана необхідність створення такого системного підходу у розрахунках. Зроблені висновки про необхідність інтеграції передових методів та моделей у єдиній методології розрахунку торсіонних валів систем підресорювання легких броньованих машин. Показана необхідність ув'язки методів напружено-деформованого стану із конструктивними, технологічними та експлуатаційними чинниками та розроблення відповідного спеціалізованого програмно-модульного комплексу для здійснення відповідних досліджень.

The requirements for the tactical and technical characteristics of the suspension systems of light armored vehicles are constantly growing, taking into account the increase in the intensity of their loads. It is necessary to improve the suspension system, in particular the torsion shafts, which are the most responsible and loaded in the suspension system of light armored vehicles. The existing traditional methods of calculating the torsion shafts of the suspension systems of light armored vehicles do not meet modern requirements. Today, there is a contradiction between the real indicators of strength and durability and those that should be provided for light armored vehicles of the new generation, and especially for future ones. In addition, this contradiction is deepened by the lack of in-depth scientific methods and models of the stress-strain state that would adequately reflect the processes and states in the torsion shafts of the suspension systems of light armored vehicles, and would also become the basis for developing measures to increase their strength and durability. The analysis of literaure showed the absence of a systematic connection of structural solutions, technological modes and load conditions in the calculations of torsion shafts of suspension systems of light armored vehicles. The necessity of creating such a system approach in calculations is shown. Conclusions were made about the need to integrate advanced methods and models in a single methodology for calculating torsional shafts of suspension systems of light armored vehicles. The necessity of linking stressstrain state methods with constructive, technological, and operational factors and developing a suitable specialized software-module complex for carrying out relevant research is shown.
Integration of advanced methods and models in the methodology of engineering calculation of torsion shafts of light armored vehicle suspension systems (review article)
Keywords: легка броньована машина; тактико-технічні характеристики; торсіонний вал; системи підресорювання; напруженодеформований стан; міцність; довговічність; пружно-пластичне деформування; контактна взаємодія; light armored vehicle; performance characteristics; torsion shaft; suspension systems; stress-strain state; strength; durability; elastic-plastic deformation; contact interaction